Entrepreneurship and SME Policies in Guinea: An Exploratory Analysis - Koropogui, Siba Théodore; St-Jean, Étienne (Journal of Comparative International Management, 2024)
This study examines the policies supporting entrepreneurship and small- and medium-sized enterprises (SMEs) in Guinea, focusing on their adequacy in fostering economic and entrepreneurial activities in a developing country context. Using the Lundström and Stevenson framework, we differentiate entrepreneurship and SME policies based on their objectives, targets, and instruments through documentary analysis. We also assess their alignment with the developmental phase and specific entrepreneurial needs. The study identifies four categories of policy instruments. These are business financing, improving the business climate, support and networking, and entrepreneurship education. However, actions favoring SMEs are more widespread than those supporting entrepreneurship. The findings underscore the importance of a holistic policy approach that balances enhancing entrepreneurial motivations, skills, and opportunities, thus fostering an ecosystem conducive to sustainable entrepreneurial growth and innovation. Additionally, the study highlights the role of entrepreneurship education in developing the necessary skills for new ventures. It suggests integrating such education into university programs to foster an entrepreneurial culture. This action could enhance employability and economic resilience, particularly among youth. By shedding light on these aspects, the research extends the theoretical framework proposed by Lundström and Stevenson to the context of low-income countries. The practical implications suggest that policymakers should consider a balanced approach to supporting nascent and established enterprises, emphasizing the need for policies that foster an inclusive and supportive environment for all stages of business development.